2018
DOI: 10.1177/1066480718809429
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Relationship Wellness Checkups With Lesbian Couples

Abstract: Relationship health impacts many facets of both physical and mental well-being, including depression, heart health, and even children's health. For a variety of reasons, distressed couples often delay entering therapy despite its value in supporting wellness and preventing distress. One early intervention program, the marriage checkup (MC), aims to keep healthy couples healthy with a brief supportive checkup. The MC is based on motivational interviewing principles, and research on MC shows the program has a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
(73 reference statements)
0
13
0
1
Order By: Relevance
“…In addition, the MC had a moderate effect size with these three transgender couples overall, which is higher than the small effect size with cisgender heterosexual couples (Cordova et al, 2014). Of note, in the pilot studies with gay and lesbian couples, the MC also had a moderate effect size (Minten & Dykeman, in preparation;Minten & Dykeman, 2019). Part of the impact of the MC on these marginalized couples may be a result of countering prejudice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the MC had a moderate effect size with these three transgender couples overall, which is higher than the small effect size with cisgender heterosexual couples (Cordova et al, 2014). Of note, in the pilot studies with gay and lesbian couples, the MC also had a moderate effect size (Minten & Dykeman, in preparation;Minten & Dykeman, 2019). Part of the impact of the MC on these marginalized couples may be a result of countering prejudice.…”
Section: Discussionmentioning
confidence: 99%
“…Fidelity of the intervention in these two previous studies used a shortened version of Cordova's fidelity assessment (M. M. Cordova, personal communication, October 1, 2014). In one study with lesbian couples, the rater gave the therapist a rating of 39 out of 40 for 98% (Minten & Dykeman, 2019). In the discussion, the rater noted the discrepancy was that the therapist phrased one question differently from the protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coop Gordon et al (2019) found the MC improved relationship satisfaction across race/ethnicity differences and income differences. The MC was helpful for cisgender heterosexual military couples (Cigrang, 2016), and cisgender lesbian and gay couples Dykeman, 2019, Minten andDykeman, 2020). The MC was successfully offered in clinic, home (Coop Gordon et al, 2019), and private practice (Trillingsgaard et al, 2016) settings.…”
Section: Marriage Checkup: An Early Intervention To Promote Couple Hementioning
confidence: 99%
“…To increase confidentiality and safety for these marginalized couples, researchers decided not to tape sessions for fidelity review. The therapist for this study was rated during two previous investigations using the MC-rating 39 out of 40 for 98% fidelity in the first study (Minten and Dykeman, 2019) and100% fidelity, and 40 out of 40 in the second one (Minten and Dykeman, 2020).…”
Section: Treatment Fidelitymentioning
confidence: 99%